STANDARD MANUFACTURING PROCEDURE OF SHADGUNA BALIJARITA MAKARADHWAJA BY ADOPTING TRADITIONAL METHOD - A PRELIMINARY STUDY (International Journal of Ayurveda and Pharma Research, 2016)
Introduction: Gandhaka Jarana is intermediate procedure for the therapeutic mercurial preparations in Ayurveda Rasashastra. For Gandhaka Jarana numerous procedures were mentioned in the classical texts of Rasashastra. Here, Shadguna Balijarita Makaradhwaja prepared in classical Valuka Yantra by adopting one of the method of Gandhaka Jarana.Objective: To prepare Shadguna Balijarita Makaradhwaja by traditional method of preparation by Valuka Yantra and to standardize its heating pattern.Materials and Methods: Shodhana of each ingredient was done followed by Kajjali preparation. Levigated and dried Kajjali was filled in KachpKupi and intermittent increasing heat was given in Valuka Yantra. Sublimed Shadguna Balijarita Makaradhwaja was obtained from neck of glass of glass bottle.Observation and results: For 16 hours heat was provided in Valuka Yantra. Average 12.77% i.e. 32.33 g yield of Makaradhwaja was obtained from all three batches of Shadguna Balijarita Makaradhwaja.Conclusion: Shadguna Gandhaka Jarana for Makaradhwaja prepared in the classical heating device Valuka Yantra by adopting addition of parts of Shuddha Gandhaka during ongoing process method; requires intermittent heat heating pattern i.e. 4.30 hours mild heat (30- 5000C), 1:30 hours moderate heat (500-6500C), and 10 hours strong heat (650-8400C).